A single terpene synthase is responsible for a wide variety of sesquiterpenes in Sorangium cellulosum Soce56. Issue 13 (7th March 2016) - Schifrin, Alexander; Khatri, Yogan; Kirsch, Philine; Thiel, Verena; Schulz, Stefan; Bernhardt, Rita
Abstract : The myxobacterium Sorangium cellulosum So ce56 is a prolific producer of volatile sesquiterpenes. Abstract : The myxobacterium Sorangium cellulosum So ce56 is a prolific producer of volatile sesquiterpenes. The strain harbours one of the largest prokaryotic genomes (13.1 Mbp). However, it codes only for three type I terpene synthases (TSs; sce1440, sce6369, sce8552) and one type II TS (sce4636), responsible for the production of at least 17 sesquiterpenes. We report here the gene expression of TSs and biosynthesis of the TS products in E. coli. Comparison with the So ce56 volatiles allows the assignment of the terpenes to their synthesizing genes. Both, the geosmin synthase sce1440 and the previously examined (+)-eremophilene synthase sce8552 are highly specific. In contrast, Sce6369, the first characterized 10- epi -cubebol synthase, is responsible for the formation of most of the So ce56 sesquiterpenes, mainly cadalanes and cubebanes. In contrast, Sce4636 does not convert FPP. Having characterized the So ce56 TSs, we screened all the 27 sequenced myxobacterial species from the NCBI and JGI-IMG databases for parent genes to predict the sesquiterpenes produced by them.